Assessment of propranolol efficacy on pediatric haemangioma: an experimental study - Fathi, Afshin; Mirzarahimi, Mehrdad (International Journal of Research in Medical Sciences, 2017)
Background: Hemangioma is the most common vascular tumor in infancy. Recent studies show Propranolol efficacy on hemangioma treatment due to its rapid effect and a few side effects. The aim of this study was to assessment the efficacy of Propranolol on pediatric haemangioma. Methods: This quasi-experimental study was done on 20 children refer to Bu-Ali hospital. Treatment indications were multiple hemangioma, organ malfunction and enlarging hemangioma. Treatment of patients was started with 1 mg/kg/day and then increased to 3 mg/kg/day and continued for 6 month. Collected data analyzed by statistical methods in SPSS-19. Results: Patients mean age was 23.2 ± 11.2 months. 65% of them were female and 35% were male. The mean size of damages was 4.9 ± 3.3 cm. 70% of patients had acceptable response with more than 50% and 30% had partial response with less than 50% decrease in size. This effect is similar to corton effect (about 84%) but with less side effects. Conclusions: This study showed that Propranolol has acceptable effect on decreasing size of hemangioma and could be recommended as a first choice of hemangioma treatment.